2022
DOI: 10.3389/fimmu.2022.880288
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a lncRNA-Based Prognostic Gene Signature Associated With Altered Immune Responses in HCC

Abstract: Hepatocellular carcinoma (HCC) is a common malignancy with higher mortality, and means are urgently needed to improve the prognosis. T cell exclusion (TCE) plays a pivotal role in immune evasion, and lncRNAs represent a large group of tumor development and progression modulators. Using the TCGA HCC dataset (n=374), we identified 2752 differentially expressed and 702 TCE-associated lncRNAs, of which 336 were in both groups. As identified using the univariate Cox regression analysis, those associated with overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 80 publications
(89 reference statements)
0
17
0
Order By: Relevance
“…The alteration of lncRNAs is also involved in immune response in cancers, including the regulation of immune checkpoint expression and tumor microenvironment composition [ 9 ]. Regarding HCC, it was shown that an up-regulated lncRNAs signature was associated with increased immune infiltration and worse overall survival [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The alteration of lncRNAs is also involved in immune response in cancers, including the regulation of immune checkpoint expression and tumor microenvironment composition [ 9 ]. Regarding HCC, it was shown that an up-regulated lncRNAs signature was associated with increased immune infiltration and worse overall survival [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that LINC01134 was highly expressed in CHOL, COAD, LAML, LIHC [7,8,19], PRAD and READ tissues compared with corresponding normal tissues (Figure S1A). Thus, further analysis was conducted to identify the correlation between LINC01134 and colorectal cancer (CRC) via the online tool GEPIA (http://gepia.cancer-pku.cn/detail.php) [15].…”
Section: Linc01134 Is Upregulated In Crc and Correlated With A Poor P...mentioning
confidence: 81%
“…LINC01133 has been shown to play an important role in the occurrence and development of gastric ( 43 ), epithelial ovarian ( 44 ), cervical ( 45 ), and pancreatic cancers ( 46 ). LINC01134 has been proven to be relevant to immune response and metabolism in hepatocellular carcinoma (HCC) and has also been identified as an effective biomarker for HCC treatment ( 47 , 48 ). Furthermore, MHENCR has been found to be a predictor of poor prognosis in CRC patients and a regulator of tumourigenesis through the inhibition of miR-532-p ( 49 ).…”
Section: Discussionmentioning
confidence: 99%